Case report: Whole-exome sequencing for a hereditary elliptocytosis case with an unexpectedly low HbA1c - Pang, Lu; Zeng, Ziyi; Ding, Yadi; Huang, Haiming; Li, Haixia (Frontiers in Medicine, 2023)
Objectives: Hereditary elliptocytosis is a group of erythroid hereditary diseases characterized by elliptically-shaped erythrocytes in peripheral blood. It is mainly inherited by autosomal dominant inheritance. This study aims to conduct a genetic etiology analysis in a case with clinical diagnosis of hereditary elliptocytosis and an unexpected low HbA 1c .Methods: Whole exome sequencing was performed to find the possible pathogenic mutations. At the same time, the bioinformatics software was used to predict the mutation function. Sanger sequencing was performed to verify the suspected pathogenic mutations.Results: Whole exome sequencing results showed that the proband with mild anemia had a heterozygous c.2303G>A (p.G768D) missense mutation in the 13 th exon of SPTB gene. The Sanger sequencing confirmed this heterozygous mutation. This mutation was extremely rare in the population and multiple software's predictions were harmful. Conservative analysis revealed that this site was highly conserved in various species.2 Conclusions: The c.2303G > A mutation of SPTB gene is the suspected cause of this patient. Our data shows that microscopic examination of red blood cells on blood smears is the important means of diagnosing hereditary elliptocytosis. Whole exome sequencing is an effective tool to determine the genetic etiology of erythrocyte membrane diseases, which can promote accurate diagnosis and genetic counseling.